Hallyu the K-Pop phenomenon a critical analysis of K-POP music. - Beguas, Ma. Veronica D.; Sinda, Krisha Kamille M. (2013.)
This thesis is a critical analysis of the factors that makes K-Pop music popular. The researchers wanted to objectively look at the music genre since there are only few studies of K-Pop despite its growing global attention in the entertainment industry. The study first traced the emergence of K-Pop, followed by the discussion of its packaging and promotion strategies as well as its implications on Philippine local music industry. The study used Commodification of Culture by Hannah Arendt and Theodore Adorno (1973) and the assumptions of Transnational media Management Theory by Barbara Parker (1996). The proponents interviewed experts: 3 from the academe, 2 from the media organizations, 2 from the music industry and 2 representatives from K-Pop fan groups and with the Director of Korean Cultural Center in the Philippines. The proponents also did library and online research. The study found out that K-Pop started mainly from K-Dramas and that combination of well-produced music and music videos, packaging and promotion strategies of Korean entertainment companies, both government and private sector efforts as well as the good adaptation to advance technologies have made K-Pop a global success.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: K-POP Music